ANALYSIS OF RELIGION AND THE CULTURE OF MALAY MARRIAGE - Evi Novianti; Yustikasari (Media Inovasi Pendidikan dan Publikasi, 2023)
Rigion has a more inherent impression on society. Religion can be regarded as a culture that has the highest level in culture itself. The similarities between culture and religion facilitate the acculturation process. The process of marriage at a custom usually does things that have been adjusted to religion. Judging from the source, religion is divided in two, namely abrahamik religion and non-abrahamik religion. Based on the cultural context, various arts occur due to the existence of history from time to time. The method used is narrative study. Data collection techniques by means of observation and in-depth interviews. The results show that the marriage procession for Malay tribes for example is a real example. In the Malay tribal wedding procession, if seen in general, it will be seen that the attachment of Islam to the tribe. This is indicated by the Khatam Quran procession. Conclusions from observations can accept this as naturally and understand that these two things are very important and cannot be separated from each other.